Galectin-1 inhibition induces cell apoptosis through dual suppression of CXCR4 and Ras pathways in human malignant peripheral nerve sheath tumors. Issue 11 (24th May 2019) - Shih, Tsung-Chieh; Fan, Yunpeng; Kiss, Sophie; Li, Xiaocen; Deng, Xiaojun Nicole; Liu, Ruiwu; Chen, Xiao-Jia; Carney, Randy; Chen, Amanda; Ghosh, Paramita M; Lam, Kit S
Abstract: Background: The Ras signaling pathway is commonly dysregulated in human malignant peripheral nerve sheath tumors (MPNSTs). It is well known that galectin-1 (Gal-1) is essential to stabilize membrane Ras and thereby induce the activation of Ras. However, the role of Gal-1 in MPNST progression remains unknown. The aim of this study was to examine whether Gal-1 knockdown could have an effect on the Ras signaling pathway. Methods: Cell viability, apoptosis assay, and colony formation were performed to examine the effects of inhibition of Gal-1 in MPNST cells. We used a human MPNST xenograft model to assess growth and metastasis inhibitory effects of Gal-1 inhibitor LLS2. Results: Gal-1 was upregulated in MPNST patients and was highly expressed in MPNST cells. Knockdown of Gal-1 by small interfering (si)RNA in Gal-1 expressing MPNST cells significantly reduces cell proliferation through the suppression of C-X-C chemokine receptor type 4 ( CXCR4) and the rat sarcoma viral oncogene homolog (RAS)/extracellular signal-regulated kinase (ERK) pathway, which are important oncogenic signaling in MPNST development. Moreover, Gal-1 knockdown induces apoptosis and inhibits colony formation. LLS2, a novel Gal-1 allosteric small molecule inhibitor, is cytotoxic against MPNST cells and was able to induce apoptosis and suppress colony formation in MPNST cells. LLS2 treatment and Gal-1 knockdown exhibited similar effects on the suppression of CXCR4 and RAS/ERK pathways. More importantly, inhibition of Gal-1 expression or function by treatment with either siRNA or LLS2 resulted in significant tumor responses in an MPNST xenograft model. Conclusion: Our results identified an oncogenic role of Gal-1 in MPNST and that its inhibitor, LLS2, is a potential therapeutic agent, applied topically or systemically, against MPNST.